Plant diversity in two horticultural farms under organic and conventional management in La Plata, Argentina: A case study - Stupino, Susana Andrea (2008)
Cultivated and associated plant diversity, were compared (the last at 3 scales: alpha, beta and gamma), in 2 farms under conventional and organic management in La Plata. The relevé method was used for associated species recording in spring and summer. At farm level we assessed total spontaneous specific richness (γ diversity), genus and family richness. Richness – species total per crop- was used as index of α diversity. We also calculated the median richness per crop sample unit. A randomization method was used to assess the degree for which differences between the observed and expected median richness per crop in a management style are attributable to chance. β diversity values were compared to a random framework, separately for each farm. Results indicate that the organic farm had higher associated diversity at all levels; also, higher number of cultivated plots and species, and proportion of exclusive, perennials, native and utilitarian species. In the organic farm crops with higher or lower median richness than expected, and higher β, indicated higher spatial and seasonal heterogeneity. Conventional management limited spontaneous plants to a reduced, homogeneously distributed group. Other factors may influence associated plant diversity.